VARIABEL PENGHAMBAT TERHADAP LATIHAN PADA PASIEN DENGAN NYERI PUNGGUNG BAWAH: SYSTEMATICAL REVIEW - Martha Sri Astuti (JPK : Jurnal Penelitian Kesehatan, 2021)
Low Back pain (LBP) is a condition that could lead to disability. The most prevalenve is amongs the productive age leads to decreasing productivity. The interventions create to solve it. It doen’t always give significant result. There are some inhibiting variables. The aim of this article ia analizing the inhibiting variables of intervention effectiveness. The methods is systematical review. The study analyzes inhibiting variables on the effectiveness of LBP intervention of 15 jounal studies. The journals quality are Q1-Q4 scopus level. The study shows that the inhibiting variables are adherence,. The journals quality are Q1-Q4 scopus level. The study shows that the inhibiting variables are the psychologic factors as obedience, adherence, environmental support and communication. As the conclusion the biopsychosocial approach could be the better one for the intervention. The technology advancement should be involved in the intervention in the future.